CARDIAC DAMAGE IN ADULT ROMANIAN POPULATION. (June 2018) - Tautu, O.F.; Darabont, R.; Dimulescu, D.; Sinescu, C.; Radulescu, L.; Oprescu, N.; Onciul, S.; Stefan, C.; Cadil, D.; Dorobantu, M.
Abstract : Objective: To evaluate the prevalence of different types of cardiac damage among the adult population of an Est-European country with very-high cardiovascular (CV) risk, using the data from SEPHAR III national survey. Design and method: A number of 1970 adults (52, 5% females, mean age 48.45 ± 17.44 years) were included in SEPHAR III survey and were evaluated for cardiac damage by: left ventricular hypertrophy (LVH) defined by left ventricular mass index (LVMi) > 115 g/m2 in males and > 95 g/m2 in females, coronary artery disease (previous history of MI, angina pectoris, myocardial revascularization, ischemic ST/T changes of pathological Q waves on 12-lead ECG tracings and segmental LV wall mouvements abnormalities), the presence of heart failure (HF) defined by previous history of HF, LVEF < 50% and or E/A < 1 or > 2 on echocardiography; and the presence of atrial fibrillation (AF) by previous history or the presence on AF rhythm on ECGs. Results: LVMi values had a mean value of 80.61 ± 26.39 g/m2 among females and 90.74 ± 27.98 g/m2 among males. LVH was detected in 314 cases representing 15.9% of the study sample. In the whole sample, a total number of 511 subjects (25.9%) had a form of CAD out of which: 209 subjects (10.9%) with history of MI of AP, 58 subjects (2.9%) with history of myocardial revascularization, 347 subjects (17.6%) with ischemic changes on ECG tracings and 78 subjects (3.9%) with segmental LV abnormal wall mouvements on echocardiography. AF was recorded among 107 subjects representing 5.4% of the study sample. A previous history of HF was recorded among 129 subjects representing 6.5% of the study sample, LVEF values recorded in the study sample had a mean value of 56.45 ± 4.69%. LV systolic dysfunction was recorded in 58 cases representing 2, 9% of the total sample, LV diastolic dysfunction defined by E/A values < 1 or > 2 was recorded in 827 cases representing 42% of the total sample. Conclusions: The results of the SEPHAR III study on cardiac damage highlights the high prevalence of this pathology among the adult population of Romania, reconfirming our country at the same time as the country with a very high CV risk.